Case report: Severe deep ulcer on the left abdomen mimicking mycosis fungoides caused by Trichophyton tonsurans in a patient with novel CARD9 mutation - Tan, Jingwen; Yu, Qian; Gao, Zhiqin; Yang, Hong; Chen, Qilong; Yang, Lianjuan (Frontiers in Immunology, 2022)
Dermatophytosis is the most common type of superficial fungal infection caused by dermatophytes. Occasionally, the fungus invades deep into the dermis or other tissues, causing deep dermatophytosis. Deep dermatophytosis is often associated with Caspase Recruitment Domain-containing protein 9 (CARD9) deficiency in patients. Here, we report the first case of deep dermatophytosis with a rare mycosis fungoides manifestation caused by T. tonsurans in a patient with a novel mutation in exon 4 of CARD9. The condition presented with heterozygous K196E mutation, which leads to deficiency of innate and adaptive immune responses in the patient, and caused intractable severe lesions. The patient received treatment with multiple antifungal drugs and was ultimately alleviated by posaconazole. These findings extend the pathogen spectrum of deep dermatophytosis linked with CARD9 deficiency and enriched their phenotypic spectrum.